(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Penetrating abdominal trauma (PAT) remains a life-threatening surgical emergency in low-resource settings, where delays in care and limited surgical infrastructure amplify mortality risks. This retrospective study analyzed 43 PATcases managed at Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Nigeria, from January 2022 to December 2023, to identify predictors of mortality and evaluate outcomes. Data on demographics, injury mechanisms, clinical presentation, surgical timing, and outcomes were extracted from medical records. The cohort predominantly comprised young males (n=38, 88.4%) aged 19–44 years (n=29, 67.4%), with gunshot wounds (n=38, 88.4%) and machete injuries (n=7, 16.3%) as leading mechanisms. Over 79.1% (n=34) underwent surgery >24 hours post-injury, often due to delayed referrals and lack of prehospital care. Overall mortality was 25.6% (n=11), with hemorrhagic shock (SBP <90 mmHg) on arrival in 44.2% (n=19) of fatal cases. Multivariate analysis identified delayed surgical intervention (OR=3.8, 95% CI:1.6–9.1), hemodynamic instability (OR=4.5, 95% CI:2.0–10.2), and lack of health insurance (OR=2.9, 95% CI:1.3–6.6) as independent mortality predictors. Complications included sepsis (n=10, 23.3%) and surgical site infections (n=8, 18.6%), disproportionately affecting uninsured patients. Violence-related injuries, particularly from communal clashes and armed robbery, accounted for 69.8% of cases, highlighting the intersection of trauma with regional insecurity. These findings underscore the lethal synergy of systemic delays, financial barriers, and violence in PAT outcomes. The study advocates for trauma system strengthening through community-first-responder networks, expanded insurance coverage, and policy initiatives to curb firearm proliferation. In resource-constrained settings, prioritizing rapid surgical access and early resuscitation may mitigate preventable deaths, while addressing socioeconomic determinants of trauma could reduce the long-term burden.